Pharmaceutical Study of Arkamanashiladi Tailam - Mrudula Divakaran; K L Virupaksha Gupta; Saravanan B (International Journal of Ayurveda and Pharma Research, 2021)
Superficial skin infections are very common in present day clinical practise. Contemporary physicians find it difficult to treat these dermatological manifestations due to long treatment duration, development of resistance and adverse drug events. Description about skin diseases are seen in Ayurveda classics like Charaka and Sushrutha under the heading of Kushta (skin diseases). Kandu (itching) is one of the primary symptoms in most of the Kshudra Kushtas. Chakradatta described a herbo mineral preparation named as Arkamanashiladi Tailam which acts as Kandughna (reduces itching) and Pamakushtahara (eradicates skin diseases). This formulation contains Arkapatra swarasa (Juice of Calotropis gigantea), Shoditha Manashila (Realgar), Nisa kalka (Paste of turmeric) and Sarshapa Tailam (Mustard oil). Preparation of Arkamanashiladi Tailam carried out according to general method of preparation of Sneha kalpana after the purification of Manashila. After considering all Pakasiddhi lakshnas like Phenodgama (appearance of froth), Shabdahina (absence of sound) etc. final product obtained which is dark brown in colour and stench smell. As there is no Analytical study reports available for Arkamanashiladi tailam to ensure its quality. Hence, in this present study different analytical parameters including Organoleptic characters, pH, Specific gravity, Refractive index, Saponification value, Iodine value, Acid value and Moisture content has been evaluated as per Ayurvedic pharmacopoeia of India. All the parameters were found to be within the reference standards and these can be used for further studies on Arkamanashiladi tailam standardization.